2008
DOI: 10.1111/j.1365-2621.2008.01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermochemical treatment on the structure of inulin and its gelling properties

Abstract: The aim of this study was to investigate rheological properties of inulin gels and the changes in the inulin structure after heating the high polymerised inulin (DP ‡ 23) solutions at different pH. The 20% inulin solutions were heated at pH 3, 5 and 7 at 60 and 80°C followed by 21 h storage at 5 and 25°C. Rheological properties evaluation indicated that the increase in the heating time and temperature significantly (P £ 0.05) influenced on the inulin structure. Reducing sugars, cryoscopy and HPLC analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 16 publications
3
48
0
4
Order By: Relevance
“…In summary: the impact of processes typical to those found in food manufacturing on inulin structure (Bohm, Kaiser, Trebstein & Henle, 2005), rheology (Glibowski & Wasko, 2008) and prebiotic activity (Huebner, Wehling, Parkhurst & Hutkins, 2008) have been investigated. The severity of functionality loss was determined by the processing conditions and aggravated by low pH and heating.…”
Section: Effect Of Fos and Inulin Degradation On Baking Is There Anymentioning
confidence: 99%
“…In summary: the impact of processes typical to those found in food manufacturing on inulin structure (Bohm, Kaiser, Trebstein & Henle, 2005), rheology (Glibowski & Wasko, 2008) and prebiotic activity (Huebner, Wehling, Parkhurst & Hutkins, 2008) have been investigated. The severity of functionality loss was determined by the processing conditions and aggravated by low pH and heating.…”
Section: Effect Of Fos and Inulin Degradation On Baking Is There Anymentioning
confidence: 99%
“…Regarding Baguette flour, an increase of breaking force was found at 12% of inulin, indicating that at a similar biscuit factor the increment of inulin increased the hardness of the biscuits (Table 4). It is known that HP inulin is able to form gels in solution (Glibowski & Wasko, 2008). It is suggested that the IN network increased the biscuit hardness.…”
Section: Resultsmentioning
confidence: 99%
“…Texture analyzer has primarily been used for assessment of rheological properties of gels used in food industry [39][40][41][42]. Several researchers have used it to characterize the rheological properties of hydrogel for drug delivery as well [43][44][45].…”
Section: Texture Analyzer Studymentioning
confidence: 99%